Regional-scale assessment of groundwater recharge and the water balance for Austria - Hanna Zeitfogel; Mathew Herrnegger; Karsten Schulz (Journal of Hydrology: Regional Studies)
Study Region: The study area covers Austria (83 900km2) and neighboring regions with transboundary river basins. Study Focus: Knowledge of regional groundwater recharge patterns is essential for sustainable water resource management. Currently, Austria lacks fully spatially distributed groundwater recharge maps. The study’s aim was to develop a nationwide hydrological model that predicts groundwater recharge and the water balance components runoff, and evapotranspiration.We implemented the rainfall-runoff model COSERO with a 1km2 spatial and monthly temporal resolution. In model calibration, four objective functions were evaluated to determine the most suitable one for our modeling purpose. Additionally, a two-stage calibration procedure was integrated to capture both water balance dynamics and low-flow characteristics. Model results were verified against independent studies. New Hydrological Insights for the Region: This study provides the first Austria-wide, fully spatially distributed groundwater recharge map for the World Meteorological Organization (WMO) reference period 1991–2020, along with updated water balance maps. We set up a consistent model framework, serving as a valuable resource for future climate change impact assessments.The model simulations yielded a long-term average groundwater recharge rate in the magnitude of 373mmyear−1, 650mmyear−1 runoff, and 538mmyear−1 actual evapotranspiration.